Top tips for interprofessional education and collaborative practice research: a guide for students and early career researchers. Issue 3 (4th May 2021) - O'Carroll, Veronica; Owens, Melissa; Sy, Michael; El-Awaisi, Alla; Xyrichis, Andreas; Leigh, Jacqueline; Nagraj, Shobhana; Huber, Marion; Hutchings, Maggie; McFadyen, Angus
ABSTRACT: Interprofessional research within the contexts of education and health and social care practice has grown exponentially within the past three decades. To maintain the momentum of high-quality research, it is important that early career researchers embarking on their first research journey and new to interprofessional education or interprofessional collaborative practice feel supported in making their contribution to the field. This guide, developed by the Center for the Advancement of Interprofessional Education (CAIPE) Research Group, has been written with these groups in mind who are embarking on their first research journey, and new to the interprofessional field. It aims to raise awareness of academic resources and share practical advice from those who have previously experienced problems when undertaking interprofessional research in education or health and social care practice.